Sistem Bagi Hasil Pertanian Milik Perseroan Terbatas Perkebunan Nusantara VIII Cisaruni Perpekstif Hukum Ekonomi Islam (Studi Kasus Di Desa Mekarjaya Kec. Cikajang Kabupaten Garut) - Gausian, Gini; Hidayatullah, Saepul (Jurnal Hukum Ekonomi Syariah, 2023)
In Mekarjaya village, Cikajang district, most are farmers and farm laborers, but not all there have their own laham, some land uses land owned by PTPN. The problems that occur in the profit sharing system in Mekarjaya village kec. Cikajang is farmers using PTPN's land to plant several types of crops that will be traded with contractors or collectors even with companies. The purpose of this study is to determine the agricultural product sharing system in Mekarjaya village, Cikajang District, Regency from the perspective of Islamic economic law related to the agricultural product sharing system. This type of research is a type of field research with a qualitative approach, which is a research that is carried out systematically by raising existing data in the field, Researchers go directly into the field to explore and examine data related to the title of this study. Based on the results of interviews with land owners, capital owners and farmers, it can be concluded that farmers do not cooperate with land owners, in this case PTPN, so farmers do not share profits with land owners. Because it turns out that PTPN only verbally allows PTPN's land to be used by farmers in Mekarjaya Village as long as PTPN does not use the land, if the land is to be reused by PTPN, the right to use the land is automatically revoked. Meanwhile, between farmers and capital owners, the agricultural system uses a muzara'ah contract. The agricultural product sharing system in Mekarjaya Mekarjaya Village is between farmers and capital owners using a muzara'ah contract because capital owners do not participate in working on agricultural land, only provide their capital to be used for farming, in other words, capital owners only wait for agricultural crops cultivated by farmers. Keywords: Profit Sharing, capital owners and landowners, Islamic economic law